2001
DOI: 10.1016/s0306-5456(01)00265-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cervical dilatation at initial presentation in labour and subsequent intervention

Abstract: Objective To examine the relationship between the cervical dilatation at which women present in labour and the subsequent likelihood of caesarean section. Design Retrospective cohort study.Setting University teaching hospital.Population 3220 women met the entry criteria from 14,050 deliveries between January 1995 and December 1999. Methods Women meeting the following criteria were identified: those in spontaneous labour with a singleton pregnancy and a cephalic presentation at 37-42 weeks of gestation; all wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 15 publications
4
64
1
1
Order By: Relevance
“…The reassurance from midwives about the normality of the slow evolution of this phase seems to be a key factor in encouraging women to stay home during early labour (Cheyne et al, 2007). It is evident that midwives often advise women in the latent phase to remain or return home in order to avoid unnecessary interventions (Bailit et al, 2005;Holmes, 2001;Rahnama et al, 2006). In most cases, women are encouraged to spend the latent phase at home with their birth partners when midwifery care at home is absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reassurance from midwives about the normality of the slow evolution of this phase seems to be a key factor in encouraging women to stay home during early labour (Cheyne et al, 2007). It is evident that midwives often advise women in the latent phase to remain or return home in order to avoid unnecessary interventions (Bailit et al, 2005;Holmes, 2001;Rahnama et al, 2006). In most cases, women are encouraged to spend the latent phase at home with their birth partners when midwifery care at home is absent.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while women in early labour usually manifest the need for support from maternity care providers, the latter often delay hospitalisation in an attempt to protect the normalcy of childbirth in consideration of the existing scientific evidence (Janssen and Desmarais, 2013;Iannuzzi and Borrelli, 2014). Several authors stated that being admitted in the latent phase would lead to higher rates of intrapartum intervention such as oxytocin augmentation, instrumental delivery or caesarean section, when compared to women admitted to hospital in active labour (McNiven et al, 1998;Holmes et al, 2001;Klein et al, 2003;Bohra et al, 2003;Bailit et al, 2005;Cheyne et al, 2006). Moreover, Lauzon and Hodnett (2009) found that early labour assessment programmes to defer the admission of women who are not in established labour may bring benefits to women at term of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Holmes P et al (2001) 24 observed that women presenting at 0-3 cm spent less time at home in labour before their first vaginal examination. The mean duration of first stage of labor was significantly higher (p<0.05) in group I which was 17.1±4.9 hours and 14.8±3.7 hours in group I and group II respectively.…”
Section: Disclosurementioning
confidence: 99%
“…It is difficult for a pregnant woman to manage timing of presentation to the hospital admission specially a nulliparous one when she is in labour. A previous study has shown that women who present to hospital at 0-3 cm spend less time in labour before presentation and are more likely to have obstetric intervention than those presenting in more advanced labour 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Admission of women who are not yet in active labour is common (30-45% of admissions) (Ball et al, 1996;Janssen et al, 2003) and has important clinical and resource implications. Several studies have reported that women admitted while not yet in labour are likely to receive higher rates of medical intervention than those admitted during the active phase (Hemminki and Simukka, 1986;Holmes et al, 2001;Jackson et al, 2003;Klein et al, 2003).…”
Section: Background To the Studymentioning
confidence: 99%